2025 Evaluability Assessments (EAs): Everything You Need to Know - CGIAR Independent Advisory and Evaluation Service (CGIAR Independent Advisory and Evaluation Service, 2025)
As CGIAR launches its new research Portfolio for 2025–2030, ensuring that each program and accelerator is ready for robust, credible evaluation is more important than ever. That’s where the Evaluability Assessments (EAs) come in. Led by the Independent Advisory and Evaluation Service (IAES), these assessments provide actionable recommendations to strengthen monitoring, evaluation, learning, and impact assessment (MELIA) systems across the Portfolio. Download the brief with all the information about EA that you need to know.